Short-term solar irradiance forecasting and photovoltaic systems performance in a tropical climate in Singapore - Nobre, André Maia (2015)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Civil, Florianópolis, 2015.